KRIM KULIT BUAH DURIAN (Durio zibethinus L.) SEBAGAI OBAT HERBAL PENGOBATAN INFEKSI JAMUR Candida albicans - Setyowati, Hanny; Hanifah, Hananun Zharfa; Nugraheni, Rr Putri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Durian rind (Durio zibethinus L.) is a part of plant that has antifungal activity. This research purposed for made extract rind of Durio zibethinus L. formula cream and tasted the physical characteristic toward Candida albicans fungi. The formulation of extract rind of Durio zibethinus L. is made with variety of extract concentration: 15%, 20%, and 25%. Cream that is produced by physically tested covers: organoleptis,homogeneity, adhesive power, dispersive power, and protection power. The result of this research showed that extract rind of Durio zibethinus L. formula cream had antifungal activities towards Candida albicans and fulfill the physically tested covers. Keywords: Durio zibethinus L, Candida albicans, cream